Pengaruh Pelatihan dan Motivasi Terhadap Kinerja Pegawai dengan Kemampuan Kerja Sebagai Variabel Intervening - Anik Rohmatul Fudla; Winarno Winarno; Wisnalmawati Wisnalmawati (Sains: Jurnal Manajemen dan Bisnis, 2021)
This research objectives to test effect of training and motivation on worker performance, and indirect work ability on the relationship between training dan motivation on worker performance. Number of research sample is 58 people. Data collecting method is census method. Data analysis used descriptive analysis and path analysis. Results of this research is revealed worker performance is affected significant positive directly by training, and motivation, and worker performance is affected significant positive indirectly by training, and motivation through work ability. Or in other words, work ability is able to mediate the effect of training and motivation on worker performance.